Relation of the Prophet Muhammad (May Peace be Upon Him) with the Byzantines from the Revelation to the Trance of the Mu'ta (8 A.H. / 629 A.D) - الدكتور علاء ابو الحسن اسماعیل العلاق (College of Education for Women, 2019)
Relations of the prophets Muhammad (May peace be upon him) with by gantlines from the revelation to the trance of al-hdybya 6 A.H/610 A.C. This research is concerned with Islamic historical events, particularly dunning the time of the prophet Muhammad. It also explores relations of the apostle of god with the rums and their allies the Arabs of Syria. During the first years of revelation Muslim had achieved great victories against the unbelievers. This accomplishm-ent had draw attention of some foreign forces such as the Arabs of Syria, who became snapicions of this new and active power. Their hostile attend was demonstrated by striking an economical siege against Muslims. They attacked the nabtins merchants whom used to provide the people of medina with their daily hiving like oil and flour, in the fifth year of al-hijra Muslim expedition had undertaken against the Arabs of Syria, which was known as Dwamat ol-Iandal. Islamic historical sources have conidial it to be the first expedition of Muhammad against the Rums. Actually this period is quite different from coming years because struggle in early stages was, in fact, between Muslims and Arab of Syria (Iakham, iutham and Kalb tribes) while in hirer period Islamic tropes had to face the roman forces them selves. Accordingly, Success in Dimwit of. Iandal was tremendously fruitful and effective at the same him exactly as prophet had planed. His main goal was to string then a brotherly relation among Muslim society, a view that had a long strategic distance and was to be the first brick in establishing the glorious state of Islam. Finally, interest of the Apostle of god in northern tribes had continued even after conquering Mecca. Many records mentioned that Muhammad (May peace be upon him) had anexpedition headed by zayad b.usam, before his death.